2006
DOI: 10.1007/s11255-006-9150-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lower urinary tract infection and bacterial stent colonization in patients with a double J ureteral stent

Abstract: Diabetes mellitus, chronic renal failure, and pregnancy are associated with a higher risk of lower urinary tract infection. Therefore, patients in these categories should be monitored carefully for infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
60
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 15 publications
16
60
2
1
Order By: Relevance
“…Unlike other institutions in which the most frequently detected microorganism is E. Coli [14][15][16]21] and Enterococci spp [13,17,19,20], the bacterial flora in our clinic seems to be different. The gram positive uropathogens and particularly staphylococcus prevailed over the rest of the gram positives and negatives.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Unlike other institutions in which the most frequently detected microorganism is E. Coli [14][15][16]21] and Enterococci spp [13,17,19,20], the bacterial flora in our clinic seems to be different. The gram positive uropathogens and particularly staphylococcus prevailed over the rest of the gram positives and negatives.…”
Section: Discussioncontrasting
confidence: 62%
“…Approximately 75% of our patients hosted at least one microorganism. This is a relatively high figure compared to other publications in which the correspond- ing rates were below 50% for a mean duration of catheterization between 2 and 9 weeks [13][14][15][16][17][18]. In only 1 paper, the adhesion rate ranged between 70 and 100% [19] and in another one, it was 90% [8].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, complications related to different types of CUUT are becoming increasingly important [18,19] . Infectious complications are the most frequent as CUUT may be associated with significant morbidity and even death [20] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Akay et al [10] reported that DM, chronic renal failure and pregnancy were risk factors for lower tract UTI in patients with D-J stent insertion. Importantly, Paz et al [11] reported that in 100 cases with D-J insertion, elective cases (non-emergent cases) had a procedure-relating febrile infection rate of 6% at the time of exchange, though comparisons were complicated by differences in the patients' backgrounds.…”
Section: Discussionmentioning
confidence: 99%